Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4314/njb.v29i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of <i>Ralstonia solanacearum</i> Causing Bacterial Wilt of Tomato in Nigeria

Abstract: Bacterial wilt of tomato, caused by Ralstonia solanacearum (Rs), is endemic in most tomato-growing areas of Nigeria, causing 60 to 100% loss in yield. Control measure requires definite information on race and biovar characteristics of the pathogen in those endemic areas. Soil samples were collected from seven states in Nigeria known for high incidence of tomato bacterial wilt. Isolations were performed on triphenyl tetrazolium chloride (TZC) and casamino peptone glucose (CPG) media. Morphological characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
5
12
0
Order By: Relevance
“…Present results agreed with those reported by [24][25][26] and Maji and Chakrabartty [27]. This is the characteristic feature of R.…”
Section: Morphological Profiling Of Ralstonia Solanacearumsupporting
confidence: 83%
“…Present results agreed with those reported by [24][25][26] and Maji and Chakrabartty [27]. This is the characteristic feature of R.…”
Section: Morphological Profiling Of Ralstonia Solanacearumsupporting
confidence: 83%
“…Moreover, the bacterium showed catalase activity and hydrolyzed starch. The result of the present study agrees with Murthy and Srinivas (2012), Alemu et al (2013), Popoola et al (2015) and Kataky, Tamuli, Teron, and Sarma (2017), who reported Gram-negativity, KOH solubility, catalase activity and starch hydrolysis of R. solanacearum.…”
Section: Identification Of R Solanacearumsupporting
confidence: 93%
“…The bacterium isolated from infected C. annum plants was identified using cultural, biochemical characters and pathogenicity test. White creamy colored, irregularly round and non-transparent colonies were formed on CPG medium which matches with the reports of Alemu, Lemessa, Wakjira, and Berecha (2013), Popoola et al (2015) and Din et al (2016). According to the Gram staining test, the isolate was found to be Gram negative.…”
Section: Identification Of R Solanacearumsupporting
confidence: 88%
“…R. solanacearum is an endemic pathogen in most of the warm environmental conditions ( Hayward, 1991 , Elsayed et al, 2020 ). The yield loss of tomato by the action of R. solanacearum is up to 60 to 100% ( Popoola et al, 2015 ). R. solanacearum can infect more than 200 plant species, especially Solanaceae, Musaceae families and other crops ( Li et al, 2014 , Mohammed et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%